How timely is access to palliative care medicines in the community? A mixed methods study in a UK city. Issue 11 (24th November 2019) - Miller, Elizabeth Jane; Morgan, Julie D; Blenkinsopp, Alison
Abstract : Objective: To investigate timely access to palliative medicines/drugs (PMs) from community pharmacies to inform palliative care service delivery. Design: Mixed methods in two sequential phases: (1) prospective audit of prescriptions and concurrent survey of patients/representatives collecting PMs from pharmacy and (2) interviews with community pharmacists (CPs) and other healthcare professionals (HCPs). Setting: Five community pharmacies in Sheffield, UK and HCPs that deliver palliative care in that community. Participants: Phase 1: five CPs: two providing access to PMs within a locally commissioned service (LCS) and three not in the LCS; 55 patients/representatives who completed the survey when accessing PMs and phase 2: 16 HCPs, including five phase 1 CPs, were interviewed. Results: The prescription audit collected information on 75 prescriptions (75 patients) with 271 individual PMs; 55 patients/representatives (73%) completed the survey. Patients/representatives reported 73% of PMs were needed urgently. In 80% of cases, patients/representatives received all PMs on the first pharmacy visit. One in five had to travel to more than one pharmacy to access PMs. The range of PMs stocked by pharmacies was the key facilitating factor. CPs reported practical issues causing difficulty keeping PMs in stock and playing a reactive role with palliative prescriptions. Confidentiality concerns were cited by other HCPs who were reluctant to share key patient information proactively with pharmacy teams. Inadequate information transfer, lack of CP integration into the care of palliative patients and poor HCP knowledge of which pharmacies stock PMs meant patients and their families were not always able to access PMs promptly. Conclusions: Consistent routine information transfer and integration of pharmacy teams in the care of palliative patients are needed to achieve timely access to PMs. Commissioners of PM access schemes should review and monitor access. HCPs need to be routinely made aware and reminded about the service and its locations.